2017
DOI: 10.4025/actascianimsci.v39i3.35112
|View full text |Cite
|
Sign up to set email alerts
|

<b>Digestibility and physico-chemical characteristics of acid silage meal made of pirarucu waste in diets for commercial laying hens

Abstract: ABSTRACT. The objective of this study was to evaluate the effects of acid silage meal made of pirarucu waste in diets for commercial laying hens on apparent digestibility and energy metabolism. Seventy-two Hisex White hens with 71 weeks of age were assigned to a completely randomized with two treatments (control diet and diet with 3% pirarucu waste acid silage) with six replicates of six birds each. phosphorus. Differences (p > 0.05) were detected in digestibility of crude protein, non-fiber carbohydrates (sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
1
7
1
8
Order By: Relevance
“…The high ash content observed may be attributed to the presence of fins, few scales and gills in the tambaqui waste. The obtained calcium (Ca) and phosphorus (P) levels are lower than those found by Batalha et al (2017) in pirarucu waste acid silage. According Sankar et al (2008), fish scales are composed of connective tissue proteins, collagen, and covered with calcium salts and other minerals, which increase the ash content of fish waste.…”
Section: Digestibility and Physicochemical Characteristics Of Tambaqumentioning
confidence: 55%
See 1 more Smart Citation
“…The high ash content observed may be attributed to the presence of fins, few scales and gills in the tambaqui waste. The obtained calcium (Ca) and phosphorus (P) levels are lower than those found by Batalha et al (2017) in pirarucu waste acid silage. According Sankar et al (2008), fish scales are composed of connective tissue proteins, collagen, and covered with calcium salts and other minerals, which increase the ash content of fish waste.…”
Section: Digestibility and Physicochemical Characteristics Of Tambaqumentioning
confidence: 55%
“…Yamamoto et al (2007) reported that freshwater fish silage has high fat content and digestibility due to its lipid composition, allowing its easy absorption by sheep. Several studies (Widjastuti et al, 2011;Rahman and Koh, 2016;Batalha et al, 2017) reported that the inclusion of fish silage in poultry diets provided high dietary nutrient digestibility.…”
Section: Digestibility and Physicochemical Characteristics Of Tambaqumentioning
confidence: 99%
“…A composição centesimal dos resíduos de pirarucu in natura encontrada no presente estudo (Tabela 1) apresentou resultados semelhantes a Batalha et al (2017) [11] e Oliveira et al (2014) [12] que obtiveram a caracterização da carcaça do pirarucu e apresentaram umidade de 68% e 79%, cinzas 1,44% e 3,42% e proteínas 15,71% e 17,56%, respectivamente. A elevada porcentagem de umidade na cabeça e carcaça in natura confirma a alta perecibilidade desses resíduos, tornando necessária a utilização de técnicas de métodos de conservação para diminuir esse teor e consequentemente aumentar a vida de prateleira do produto final, controlando as alterações físicas, químicas e principalmente as microbiológicas [13].…”
Section: Resultsunclassified
“…Na Tabela 3, o filé do pirarucu apresenta uma quantidade de minerais inferior à dos resíduos, tanto da cabeça como da carcaça, apesar da carcaça ter apresentado um valor mais alto neste trabalho (3,38%), se diferindo estatisticamente do conteúdo da cabeça (1,60%) a 5% de significância pelo teste de Tukey. Após a liofilização e concentração de proteínas, o valor de cinzas aumentou (Tabela 3) e essa diferença na composição está relacionada com a retirada de umidade e concentração dos nutrientes [11]. Na Tabela 4, observa-se que o teor de proteínas para os resíduos liofilizados apresentou valor superior (31,57% e 34,59%) ao do filé.…”
Section: Resultsunclassified
“…Em meio aos benefícios encontrados pela ingestão de pescado, identifica-se a redução dos níveis de colesterol, redução de casos de acidente vascular cerebral, doença cardíaca, Alzheimer, ampliação da função cognitiva em adultos e menor índice de crianças com baixo peso e prematuras (Sartori & Amâncio, 2012). Research, Society andDevelopment, v. 10, n. 1, e23510111698, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i1.11698 Desta forma, há apontamentos em relação à qualidade nutricional do pescado, sobretudo, por ser fonte de proteínas de alto valor biológico (Batalha et al, 2017), e por apresentar valores de minerais e vitaminas lipossolúveis (Sakabe et. al., 2013), além de micronutrientes como fósforo, ferro, cobre, selênio, iodo, ácidos graxos poliinsaturados ω-3, 6, 7 e 9 e proteínas importantes para a manutenção celular, equilíbrio metabólico e controle do colesterol (Mahan et al, 2018).…”
Section: Introductionunclassified